Relationship Knowledge And Attitude Of Pregnant Women Aboutanemia Incidence At The Mamboro Community Health Center - Nurhaeda Nurhaeda; Kasmiati Kasmiati; Aisyah Aisyah; Fadly Fadly (Lembaga Pengembangan Kinerja Dosen, 2022)
Background. Anemia during pregnancy is still a major problem in the world today because it is one of the causes of maternal death or also known as